A Financial Capitalism Perspective on Start-Up Acquisitions: Introducing the Economic Goodwill Test. (10th September 2020) - McLean, Andrew P
Abstract: This paper discusses the acquisition of start-ups by major technology firms. Such transactions pose a significant anticompetitive threat, yet often escape competition scrutiny because they fail to trigger merger notification threshold tests. Alongside a financial analysis of historic acquisitions by Google, Apple, Facebook, Amazon and Microsoft, the paper introduces a new threshold test—the economic goodwill test. The economic goodwill test is a concerned with the value of a target's net tangible assets as a proportion of total transaction value. The difference between these figures largely represents the gains an acquirer expects to realise from a strengthened competitive position, therefore reflecting the logic driving the mass acquisition of technology start-ups. Although a specific triggering figure is not prescribed, the economic goodwill test represents a useful innovation that could bring potentially anticompetitive start-up acquisitions under substantive merger review. More broadly, the paper argues start-up acquisitions are representative of the difficulties that competition law faces governing economic activity in the era of financial capitalism. The modern financial system creates a strong bridge between the present and the distant future. This enables firms to engage in future-oriented competitive strategies that challenge competition law's static approach.